2023
DOI: 10.1126/science.adf2160
|View full text |Cite
|
Sign up to set email alerts
|

Wild pedigrees inform mutation rates and historic abundance in baleen whales

Marcos Suárez-Menéndez,
Martine Bérubé,
Fabrício Furni
et al.

Abstract: Phylogeny-based estimates suggesting a low germline mutation rate (μ) in baleen whales have influenced research ranging from assessments of whaling impacts to evolutionary cancer biology. We estimated μ directly from pedigrees in four baleen whale species for both the mitochondrial control region and nuclear genome. The results suggest values higher than those obtained through phylogeny-based estimates and similar to pedigree-based values for primates and toothed whales. Applying our estimate of μ reduces prev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 95 publications
2
5
0
Order By: Relevance
“…In the North Atlantic, our pre-whaling NE translated into abundance approximately nine times lower (~ 40,000 individuals) than earlier single locus genetic estimates (Roman & Palumbi, 2003) 360,000 individuals, (Roman & Palumbi, 2003). Our recent demographic results were generally consistent with prewhaling population estimates based on historical records or pedigree-based mutation rates (Sergeant, 1977;Suárez-Menéndez et al, 2023). However, the results here are sensitive recombination and mutation rates, as well as generation time (Kardos et al, 2017).…”
Section: 2bsupporting
confidence: 77%
See 4 more Smart Citations
“…In the North Atlantic, our pre-whaling NE translated into abundance approximately nine times lower (~ 40,000 individuals) than earlier single locus genetic estimates (Roman & Palumbi, 2003) 360,000 individuals, (Roman & Palumbi, 2003). Our recent demographic results were generally consistent with prewhaling population estimates based on historical records or pedigree-based mutation rates (Sergeant, 1977;Suárez-Menéndez et al, 2023). However, the results here are sensitive recombination and mutation rates, as well as generation time (Kardos et al, 2017).…”
Section: 2bsupporting
confidence: 77%
“…Pre-whaling abundance has been the subject of considerable interest and debate as the degree of endangerment of contemporary baleen whale populations is scaled against the historic abundance (Roman & Palumbi, 2003;Suárez-Menéndez et al, 2023;Tulloch et al, 2018;Zerbini et al, 2019). The whole-genome LD-based approach employed in this study suggested that whaling reduced the abundance of the two species in this specific population by 97-98%, confirming the devastating effects of the mechanized, highly effective industrial whaling operations in the Southern Ocean (Rocha, Jr. et al, 2015;Zerbini et al, 2019).…”
Section: Pre-and Post-whaling Abundancesupporting
confidence: 56%
See 3 more Smart Citations